DETERMINANT OF FRAUD PENTAGON IN DETECTING FINANCE OF FINANCIAL STATEMENTS - Bagus, Muhammad; Rizal, Noviansyah; Desi Lastianti, Siwidyah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This study aims to determine the Pentagon Determinant Fraud in detecting fraudulent financial statements. Fraudulent financial statements are proxied by the Fraud Score Model. Whereas the pressure factor is proxied by insisting from within, for the opportunity factor proxied by industry conditions, the rationalization factor is proxied by the ratio of total accruals, the competency factor is proxied by the change of directors and arrogance is proxied by the duality of quality positions at the CEO. The population in this study amounted to 100 companies incorporated in the compass index 100 contained in the Indonesia Stock Exchange and for the sample of the study were 35 companies belonging to the compass index 100 contained in the Indonesia Stock Exchange, which was selected using the purposive sampling method for the 2017-2018 period. Data were analyzed using multiple linear regression. Based on the test results, it was concluded that the pentagon fraud component included internal pressure (LEV), industry conditions (INVENTORY), rationalization (TATA) influencing financial statement fraud while competence (DCHANGE) and arrogance (DCD) had no effect on financial fraud statement. This proves that internal pressure (LEV), industry conditions (INVENTORY), and rationalization (TATA) can be used to detect fraud in financial statements.